PENETAPAN TARIF BERDASARKAN ANALISIS BIAYA SATUAN PADA PELAYANAN KESEHATAN RAWAT JALAN TINGKAT PERTAMA PUSKESMAS DI KABUPATEN BANYUMAS - Arih Diyaning Intiasari; Arif Kurniawan (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Research to assess the amount of real costs for the provision of RJTP health care of Puskesmas in Banyumas as the basis for determination of tariff policy. The results show the unit cost of health care which considering total cost without investation is greater than tariff set by the The goverment of Banyumas regency. Average unit costs for health care in BP was Rp. 5846, unit-cost of MCH / family planning is Rp. 6775, - but the average unit cost in the BPG reached a high nominal, it is Rp. 23 724. Determination of tariff that was being applied in RJTP Banyumas is Rp. 5.000, - for the BP service and MCH / family planning, and for BPG service is Rp.8.000. The current tariff is lower than the unit cost of service. This research suggests that it is necessary to have unity of perceptions toward stakeholders in government of Banyumas regency about the benefits of unit cost analysis in determining the tariff policy in the future, and it suggests to do research about Ability and Willingness to Pay in order to obtain more rational and competitive tariff determination and calculation in regency of Banyumas. Kata Kunci: Unit cost, tarif pelayanan, puskesmas Kesmasindo. Volume 4(1) Januari 2011, hlm. 81-94